Analisis Butir Soal Bahasa Indonesia Ujian Semester Genap Kelas VII SMP Negeri 8 Pekanbaru Tahun Pelajaran 2019/2020 - Muhajjir, Redho; Nazirun, Nazirun (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
This research is entitled "Analysis of Indonesian Language Questions for Even Semester VIII Class SMP Negeri 8 Pekanaru for the 2019/2020 Academic Year". The problems described in this study are: (1) How to write Indonesian language questions for the even semester exams for class VIII SMPN 8 Pekanbaru in the 2019/2020 school year on the question material aspect?, (2) How to write Indonesian language questions for the odd semester exams for class VIII SMPN 8 Pekanbaru for the 2019/2020 school year on the question construction aspect? The theory used is the 2008 Ministry of National Education, Arikunto 1992, Nurgiyantoro 2014, and other supporting theories. The research approach is a quantitative type of field research and (field research) and library (library research) the method used is descriptive. Source of research data on odd semester examinations in Indonesian for class VIII SMP Negeri 8 Pekanbaru for the 2019/2020 school year. The results showed that the analysis of the items for the Even Semester Examination of Indonesian Language Subjects for Class VIII of SMP Negeri 8 Pekanbaru, Marpoyan Damai District for the 2019/2020 Academic Year, in the material aspect of the questions, 45 items showed (90%), and 5 items were not good. the questions show (10%) and are categorized as very good (86-94) thus the hypothesis is rejected. While in the construction aspect, 44 items show good questions (88%), and 6 items that are not good show (12%) and are categorized as very good (86-94) thus the hypothesis is rejected